Análise comparativa do sistema educativo de formação inicial do professor para a educação básica - Santos, Heinrich da Solidade (2019)
This dissertation refers to the research of the Professional Master's Degree in Science and Mathematics Teaching, of the Graduate Program in Teaching of Sciences and Mathematics, Federal University of Uberlândia, with the purpose of proposing investigations to the research problem: what are the confluences and divergences of the supranational public educational policies that make up the Mercosur countries, which aim at the initial formation of teachers for Basic Education? The general objective is to analyze, through the Comparative Education Methodology, the confluences and divergences of the educational policies aimed at the initial formation of teachers for Basic Education in relation to the countries that are of the nucleus of States Parties of Mercosur. For this purpose, as specific objectives, it is proposed: (1) to understand the conceptions of the Comparative Education Methodology and the challenges of Teacher Training in Latin America; (2) understand the historical, socio-political and educational context of the Mercosur Member States; (3) to investigate the official documents that propose the educational conceptions for Basic Education in each country; (4) develop, as educational products, digital media; and (5) make available on online platforms, through a publisher, in the form of an e-book, which will aim at teacher education under the educational conceptions of Argentina, Bolivia, Brazil, Paraguay and Uruguay. In order to identify the degree of similarity or difference between the objects analyzed, this research is based on the Methodology of Comparative Education, addressing the phases of this methodology, through: methodological design; description and interpretation; juxtaposition and comparison. In this context, the juxtaposition and comparison, as a result of the Tree of Categories, advocated in the Methodology of Comparative Education, have as guiding axes: (a) Sociopolitical and educational context of the States Parties; (b) Legislative and economic trajectories of initial training of States Parties; (c) Paradigm of initial teacher training in States Parties; and (d) Admission of teachers to the profession in the States Parties. It was noted that those responsible for and interested in socio-political and economic development in the educational systems of Mercosur member states could mirror the models of access to institutions and share ideas that provide the best use of the teacher training process, so that consider the multicultural scenario of the Latin American region. It was noted that there is a need for States Parties to broaden the dialogues, seeking proposals for similar social, political and educational problems that affect the quality of Basic Education. In order to improve quality teacher education, it is necessary to take into account regional and cultural specificities, providing the actors involved with education with a professional appreciation approach. Thus, the development of the identity of the teacher, located in Mercosur, can be contemplated through more experiences that help him to understand the knowledge that will support him in his practice.